2020
DOI: 10.28991/scimedj-2020-02-si-6
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Related Challenges and Advice from Parents of Children with Autism Spectrum Disorder

Abstract: With the rise of the COVID-19 pandemic and shelter-in-place, families with children with autism spectrum disorder (ASD) face a unique set of challenges related to a diverse set of issues. A qualitative study was conducted in the form of semi-structured interviews from fifteen parents of children and adolescents from a non-public school for children with ASD. Questions covered the following topic areas: general COVID-19 experiences and concerns, changes in the child’s mood and behavior, changes in parent mood a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 16 publications
(18 reference statements)
1
15
0
5
Order By: Relevance
“…Children going to school regularly before the pandemic showed new-onset behavioral issues during the lockdown, potentially due to sudden unanticipated disruption of routine and structured care similar to other studies. [ 11 23 24 25 26 ] These children were also in contact with the psychiatrist, indicating previously existing behavioral issues and/or better awareness of behavioral issues among parents. These parents also attended training programs and reported positive changes in children, possibly indicating that children going to school regularly also were those with better skills and milder forms of ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children going to school regularly before the pandemic showed new-onset behavioral issues during the lockdown, potentially due to sudden unanticipated disruption of routine and structured care similar to other studies. [ 11 23 24 25 26 ] These children were also in contact with the psychiatrist, indicating previously existing behavioral issues and/or better awareness of behavioral issues among parents. These parents also attended training programs and reported positive changes in children, possibly indicating that children going to school regularly also were those with better skills and milder forms of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, Parenteau et al also found that having a routine, and creating schedules offer parents opportunities to prevent burnout and facilitate quality use of time at home for individuals with ASD. [ 24 ] However, the proportion of families following such interventions needs to be increased through appropriate interventions.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that mask wearing by "non-sick" people could potentially block the spread of contagious droplets from asymptomatic patients during social activities as well as provide the wearer with a symbol to enhance the awareness of protective measures and generate a sense of safety and well-being. Nonetheless, multiple factors should be taken into consideration before implementing a universal mask policy in a healthy population, including cultural differences, scientific evidence in different settings, adequacy of perceived knowledge on mask use in the general population, adaptation difficulties in people with special needs and, most importantly, the scarcity of resources and logistic support [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…We are also currently facing previously unknown situations like mass temporary unemployment, working from home, online homeschooling, rise in domestic violence, absolute lack of physical contact with friends/family, and restrictions within home space for prolonged periods (Colizzi et al, 2020;Di Renzo et al, 2020;Frankova, 2020;Kawabe et al, 2020;Parenteau et al, 2020). In parallel, fear of contracting the virus is still widely prevalent (Rajkumar, 2020;Roy et al, 2020;Singh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%